A case of severe transient sinus bradycardia in herpes simplex infection - Wan Mahmud Sabri, Wan Muhammad Najib; Yahaya, Nor Azni; Alias, Amelia; Anuar, Muhamad Azamin (Faculty of Medicine and Health Sciences, UPM, 2021)
Herpes simplex virus remains the commonest organism of sporadic encephalitis. Common presentations in herpes simplex encephalitis are seizures and behavioural changes apart from fever, lethargy and headache. Cardiac manifestations, nonetheless, are uncommon in herpes simplex infection. We presented an 8-year-old boy with clinical meningoencephalitis and bradycardia. The initial impression was typhoid meningitis due to severe bradycardia. He was managed in paediatric intensive care unit with transcutaneous cardiac pacemaker and infusion of low dose noradrenaline until the bradycardia resolved. A diagnosis of herpes simplex encephalitis was made based on clinical and specific right temporal and focal radiological findings including right insular ribbon involvement, focal changes over temporal and frontal electroencephalographic (EEG) inference and positive HSV IgM serological confirmation.